Public trust in the national assembly of Republic of Korea revisiting trust antecedents - MOON, Yeonkyung (KDI School, 2016)
Despite the high quality of representative democracy and nation-wide structural reforms to transparency and openness in the Republic of Korea, public trust in National Assembly has scored the lowest level of all public institutions and is still worsening. In this paper investigates the reasons of low public trust in National Assembly and distinguishes which trust antecedents have caused the severe public distrust in it. Moreover, based on trust frameworks specifically tailored to current National Assembly, this paper aims to analyze three major trust antecedents (Competency, Benevolence, and Integrity) and corresponding trust antecedents in details. Following the 1:1 focus-group interviews and survey results, the effects of trust antecedents on public trust in National Assembly are examined.
Thesis(Master) --KDI School:Master of Public Policy,2016